Implementation of SOAR analysis in school development at SDN Pelambuan 4 Banjarmasin - Anugrah Mitria Sari; Wafa Nur Azizah; Muhammad Fitriadi; Irma Irma; Ria Aprianti; Ahmad Suriansyah; Ratna Purwanti (HAFECS PRESS, 2026)
The implementation of strategic management in elementary schools is still dominated by problem-based approaches such as SWOT, while studies on the application of SOAR Analysis (Strengths, Opportunities, Aspirations, Results) as an appreciative and strength-based approach remain limited. Furthermore, previous research has not extensively explained how the four dimensions of SOAR are systematically applied in school development. This study aims to analyze the implementation of SOAR Analysis in school development at SDN Pelambuan 4 Banjarmasin. The study employs a qualitative approach using a case study design. Data were collected through interviews, observations, and document analysis involving five informants: one school principal, two teachers, one school staff member, and one school committee chairperson. Data validity was ensured through triangulation of sources, methods, and time, as well as member checking. Data analysis utilized the Miles and Huberman interactive model, with findings grouped according to the four SOAR components. The research findings indicate that the strengths dimension is reflected in a collaborative culture, competent human resources, and adequate digital facilities. The opportunities dimension stems from government policy support, the School Driver Program, and strategic partnerships with various stakeholders. The aspirations dimension is realized through the school’s “TERMUDA” vision (Berkarakter, Berilmu, Berbudaya) as the direction for school development. The results dimension is evident in improved teacher collaboration, learning quality, student achievement, stakeholder participation, and data-driven school management. Thus, the SOAR Analysis has proven to be an effective strategic framework for fostering appreciative, collaborative, and sustainable school development. Abstrak. Implementasi manajemen strategik di sekolah dasar masih didominasi oleh pendekatan berbasis masalah seperti SWOT, sedangkan kajian mengenai penerapan Analisis SOAR (Strengths, Opportunities, Aspirations, Results) sebagai pendekatan apresiatif dan berbasis kekuatan masih terbatas. Selain itu, penelitian sebelumnya belum banyak menjelaskan bagaimana keempat dimensi SOAR diterapkan secara sistematis dalam pengembangan sekolah. Penelitian ini bertujuan menganalisis implementasi Analisis SOAR dalam pengembangan sekolah di SDN Pelambuan 4 Banjarmasin. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Data dikumpulkan melalui wawancara, observasi, dan studi dokumentasi terhadap lima informan yang terdiri atas satu kepala sekolah, dua guru, satu tenaga kependidikan, dan satu ketua komite sekolah. Keabsahan data dilakukan melalui triangulasi sumber, teknik, dan waktu serta member checking. Analisis data menggunakan model interaktif Miles dan Huberman dengan pengelompokan temuan berdasarkan empat komponen SOAR. Hasil penelitian menunjukkan bahwa dimensi strengths tercermin pada budaya kolaboratif, sumber daya manusia yang kompeten, dan fasilitas digital yang memadai. Dimensi opportunities berasal dari dukungan kebijakan pemerintah, Program Sekolah Penggerak, serta kemitraan strategis dengan berbagai pihak. Dimensi aspirations diwujudkan melalui visi sekolah “TERMUDA” (Berkarakter, Berilmu, Berbudaya) sebagai arah pengembangan sekolah. Dimensi results tampak pada peningkatan kolaborasi guru, kualitas pembelajaran, prestasi siswa, partisipasi pemangku kepentingan, serta pengelolaan sekolah berbasis data. Dengan demikian, Analisis SOAR terbukti menjadi kerangka strategis yang efektif dalam mendorong pengembangan sekolah yang apresiatif, kolaboratif, dan berkelanjutan.